2018
DOI: 10.1038/s41598-018-19385-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of left atrial appendage morphology on thrombus formation after successful left atrial appendage occlusion: Assessment with cardiac-computed-tomography

Abstract: A standardized imaging algorithm by cardiac computed tomography angiography (cCTA) (LOVE-view) was used in 30 patients to evaluate the influence of different left atrial appendage (LAA) morphologies on development of thrombosis in the LAA 6 months after implantation of an occlusion device (Watchman or Amplatzer-Cardiac-Plug) in patients with non-valvular atrial fibrillation, CHA2DS2-VASc-Score >1 and a contraindication for oral anticoagulation. The distribution of different LAA morphologies was 40% windsock, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…Earlier studies have reported chicken‐wing shape to be a challenging LAA morphology for Watchman deployment with significant impact on implantation success and compression ratio 16 . Furthermore, in a study by Dieker et al, 17 rate of complete thrombosis in the LAA was the lowest in the chicken‐wing type, which was in agreement with our data.…”
Section: Discussionsupporting
confidence: 93%
“…Earlier studies have reported chicken‐wing shape to be a challenging LAA morphology for Watchman deployment with significant impact on implantation success and compression ratio 16 . Furthermore, in a study by Dieker et al, 17 rate of complete thrombosis in the LAA was the lowest in the chicken‐wing type, which was in agreement with our data.…”
Section: Discussionsupporting
confidence: 93%
“…The prevalence of LAA patency was 67% among patients in studies using delayed phase imaging compared with 60% in those using only early phase imaging. (10,12,13,14,20,21,22,23,24) (Supplementary file; table). Two studies (11,25) reported LAA assessment in early and delayed phase techniques, which detected a 25% to 50% higher prevalence of LAA patency on the delayed imaging.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Clinical outcomes, including stroke, TIA, or DRT, were reported in 14 studies. (10,12,13,14,15,16,17,18,19,20,21,22,23,24) None of these compared outcomes between patient groups based on the presence or absence of LAA patency or DRT. Moreover, a wide clinical follow-up span was observed, with a median value of 377.5 (222-758.3) days.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Despite using this regimen, thrombus formation on the Watchman device is not uncommon. Predisposing factors for the development of thrombus are multifactorial including patient- and device-related factors [4]. These factors include but are not limited to prior thromboembolism, high CHA2DS2-VASC score, and deeply implanted device or large device [5, 6].…”
Section: Discussionmentioning
confidence: 99%